Sensibilidade e agência: reverberações entre corpos sonoros no mundo Tikm'n-Maxakali - Jose Ricardo Jamal Junior (2012)
This study aims to understand how are considered by the Tikm'n/Maxakali, indians inhabitants of extreme northeast of Minas Gerais, some of the sound events that take place in their villages. From ethnographic data as well as myths collected by other researchers, it has been found that what inicially was called by musical instruments, did not lend itself well to be thought of as passive objects as has been done in the context of certain organologies. Rather, the sound production in the context studied operates transformations, sometimes in a cosmic level. In order to sketch brief comparisons, these informations were colatted with Lévi- Strauss' indications, which are in From Honey to Ashes and that are linked with the sound events concerning the amerindian world, especially those presented in mythological narratives, and with other ethnographies. Finally, it was considered that there aren't, here, objects, but rather bodies, in view of the agentive quality that seemed to characterize them. They are, themselves, sonorous bodies, but that also echo the sound of other bodies. They are multiples bodies.